2019
DOI: 10.32098/mltj.03.2013.09
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of sports injuries and athletic performance

Abstract: Purpose: in the last two decades, several evidences have been provided to support the relationship between single nucleotide polymorphisms and the susceptibility to develop injuries participating in sport and performance related to sports activity. We report up-to-date review of the genetics factors involved in tendon injuries and athletic performance. Methods: we searched PubMed using the terms "sports injuries", "athletic performance" and "genetics" over the period 1990 to the present day. We also included n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 168 publications
(255 reference statements)
0
48
0
5
Order By: Relevance
“…Secondly, the patellar and Achilles tendons have somewhat different architecture, location, and function, which should be taken into account when considering factors related to genetic regulation. Lastly, keeping in mind that the pattern of genetic variation is closely linked to ethnic background, results from previous genetic association studies in the field of tendinopathy are based on different populations (South African, Australian, British, and Caucasian) with different genetic makeup as a complicating factor …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the patellar and Achilles tendons have somewhat different architecture, location, and function, which should be taken into account when considering factors related to genetic regulation. Lastly, keeping in mind that the pattern of genetic variation is closely linked to ethnic background, results from previous genetic association studies in the field of tendinopathy are based on different populations (South African, Australian, British, and Caucasian) with different genetic makeup as a complicating factor …”
Section: Discussionmentioning
confidence: 99%
“…The G to T base transition located within intron 1 of the COL1A1 gene (chromosome 17) has been proposed as a functional sequence variant, and several case-control studies have examined whether this variant is associated with tendon disorders, such as anterior cruciate ligament and Achilles tendon ruptures. [18][19][20][21] The role in overuse injuries and tendinopathy is less documented, and the variant has never been examined for a potential association with patellar tendinopathy. Nevertheless, all of the studies referred above found the homozygous T/T group to be underrepresented in the injured study groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative polymorphic variants of these candidate polymorphisms were demonstrated to be associated with sprint/power or endurancerelated disciplines with reasonable replication in different groups of athletes (15)(16)(17)(18). Indeed, the Iallele of the insertion(I)/deletion(D) polymorphism in the ACE gene is one of the most suggested determinant of aerobic capacity in endurance-oriented performance (8). Similarly, the PPARɑ G, the ACTN3 X and the CK-MM A alleles are all involved in contributing to improved aerobic performance (16,17,19).…”
Section: Introductionmentioning
confidence: 97%
“…Athletes of mixed sport disciplines are not clearly "endurance" or "power" oriented, thus showing a wide phenotypic heterogeneity (7). It is well established that sprint/power and endurance capacities are influenced by genetics (8) but few studies have examined the link between genetic factors and athletic performance in mixed athletes. Among the candidate polymorphisms potentially associated with muscle function and physical performance, the most extensively studied are the angiotensin-converting enzyme (ACE), the R577X variant of the actinin-α 3 gene (ACTN3), the muscle isoform of creatine kinase (CK-MM), the peroxisome proliferator-activated receptor α (PPARα) and recently the SLC2A4 (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%